Integrated scheduling, assembly area- and part-assignment for large scale, make-to-order assemblies - Rainer Kolisch (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1998)
The problem of scheduling multiple, large scale, make-to-order assemblies is considered. Beside "classical" precedence- and resource constraints as known from resource constrained project scheduling we take spatial resource and part availability constraints into account. The objective is to minimize the sum of the weighted tardiness. We propose a MIP-model of the problem which is a generalization of three allocation problems. Since the problem is NP-hard, a list-scheduling heuristic is proposed and evaluated on a set of benchmark instances.
Keywords: 650; Produktionssteuerung; Scheduling-Verfahren; Auftragsfertigung; Theorie